Pengaruh Migrasi terhadap Konsep Kewarganegaraan di Negara-Negara Maju - Masayu Anas Tasya; Adinda Mila Sari; Hania Safitri Ramadhani; Ilham hudi; Annastasya Amalia Putri; Muhammad Fathir (Lembag, 2024)
This study aims to analyze the influence of migration on the concept of citizenship in developed countries. Adopted the literature review method by investigating 10 journal articles published between 2000 and 2019. This research aims to understand how international migration flows affect the definition and practice of citizenship. Migration between countries in the era of globalization is something that cannot be prevented or avoided. Motives underlying the movement of labor between countries or international migration. The first motive, they work abroad with the aim of selling their energy, skills or cleverness. Usually the main stream of labor flows of this motive comes from developing countries to developed countries, or from poor countries to rich countries, or from labor-surplus countries to countries experiencing labor shortages. The second motive is that they work abroad in connection with the sale of technology or capital investment. The mainstream of this second motive is generally from developed countries to developing countries. These findings underscore the need for more inclusive and adaptive policy adjustments to deal with the social changes resulting from migration.